(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The Federal University of Alagoas plays a leading role in the production of knowledge and the training of professionals in Alagoas. Its services and activities are disseminated by the Communications Office which, despite its potential, deals with the absence of an institutionalized policy. The aim of this paper is to discuss the institution’s historical and social configurations and to present aspects of the work of the Communications Office, using documentary and bibliographical research, through an exploratory and qualitative study. The results show the social function of the university, as well as the need to view the sector strategically.